2017
DOI: 10.1016/j.conbuildmat.2016.11.114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of filler nature and content on the bituminous mastic behaviour under cyclic loads

Abstract: The role of the filler in asphalt mixtures is particularly important because of its influence on mastic behaviour. The filler improves the resistance properties of bitumen against the action of traffic loads and temperature. However, the filler can also adversely affect bitumen in mastics excessively brittle and stiff due to inappropriate design. For these reasons, it is interesting to investigate the effect of filler type and content on mastic composition. This paper presents results from a strain sweep test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Although the Superpave Mix Design Manual SHRP A-407 [22] indicates that filler proportion has to be defined as 'the ratio of the percent by weight of aggregate passing the 75 mm sieve to the effective asphalt binder content expressed as percent by weight of the total mix', it is commonly acknowledged that volumetric proportioning of filler in mastics could affect the physical and rheological behaviour [37,38]. This is also recognised by [22].…”
Section: Resultsmentioning
confidence: 99%
“…Although the Superpave Mix Design Manual SHRP A-407 [22] indicates that filler proportion has to be defined as 'the ratio of the percent by weight of aggregate passing the 75 mm sieve to the effective asphalt binder content expressed as percent by weight of the total mix', it is commonly acknowledged that volumetric proportioning of filler in mastics could affect the physical and rheological behaviour [37,38]. This is also recognised by [22].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the test protocol induces failure in a significantly shorter period than if a constant strain amplitude (time-sweep) was maintained. This test protocol has been successfully implemented before with bitumens and mastics at different temperatures [14,16]. Hence, one of the advantages of this test protocol is that it allows testing at lower temperatures (< 15ºC) than is often possible with the dynamic shear rheometer [22].…”
Section: Uniaxial Strain Sweep Test (Ebade)mentioning
confidence: 99%
“…From this, uniaxial tension-compression cyclic tests have been proposed to evaluate the cracking resistance of bitumen and mastics [14,15]. Miró et al [16,17] showed the ability of this type of test to differentiate the fatigue behaviour of different bitumens, on various conditions of ageing and temperature, and to evaluate the effect of filler incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…A good workability (and compactibility) leads to reduction of the mix air voids during the mixing process, provides aggregates interlock, eventually improves the final asphalt layer stiffness, and increase its moisture resistance. Compaction of mixes was found to depend on aggregate gradation in term of nominal maximum aggregate size (NMAS) [22], on the type, shape, and texture of aggregate [23,24], content and lithological nature of filler [25][26][27][28]; mixing and compaction temperature are related to content, grade and type of bitumen [24,29] and on indoor compaction methods [30][31][32].…”
Section: Introductionmentioning
confidence: 99%